Sustainability Beton Metode Life Cycle Assessment Studi Kasus: Limbah Beton Laboratorium Bahan dan Konstruksi Departemen Teknik Sipil Universitas Diponegoro Semarang - Sapulete, Christhy Amalia; Lie, Han Ay; Priastiwi, Yulita Arni (MEDIA KOMUNIKASI TEKNIK SIPIL, 2018)
Sustainability is an effort to build an infrastructure by considering the environmental impacts that occur. Concrete production as a construction material that commonly used in infrastructure development is one contributor to carbon dioxide (CO2) emissions. CO2 is produced from the calcination process in the manufacture of cement, burning of fossil fuels, and electrical energy used. More specifically by reviewing the calcination process on cement making, it has evaluated the consumption of cement in concrete production. The Life Cycle Assessment (LCA) is an environmental impact evaluation in terms of the life cycle of a product, wherein this paper, using the cradle-to-cradle scope, LCA is used as a method to evaluate cement consumption in concrete production to concrete waste management by taking concrete waste at Construction Laboratory and Materials Diponegoro University, Semarang for the case study. The results of the evaluation stated that the use of geopolymer concrete with fly ash as a substitute for cement could reduce up to 80% CO2 emissions with concrete strength 75% larger than conventional concrete. And for the concrete waste management, Construction Laboratory and Materials Diponegoro University reused concrete cylinder waste as a substitute material to build the retaining wall.